The PATH Protocol for Integrated Facial Rejuvenation: A Preliminary Three-Patient Case Report Series and Narrative Review of the Literature - Enrica Filigheddu; Luigi Sardellitti; Manuela Astrid Chessa; Edoardo Filigheddu; Alessio Pirino; Egle Patrizia Milia (Reports, 2026)
Background and Clinical Significance: Facial aging is a multifactorial process involving the skin, subcutaneous tissues, facial fat compartments, muscles, ligaments, and skeletal structures. Integrated minimally invasive protocols are increasingly used to improve facial harmony and skin quality while preserving natural expression. The PATH (Profundity, Action, Timing, and Home care) protocol combines chemical peeling, hyaluronic acid–succinate filler, intradermal biorevitalization, and post-procedural homecare in a sequential and individualized approach to facial rejuvenation; Case Presentation: Three female patients aged 52–58 years with clinical signs of facial aging were treated according to the PATH protocol. Assessments were performed at baseline and after 60 days using standardized photography, OBSERV 520®, Antera 3D PRO®, and QuantifiCare LifeViz® Infinity Pro. No serious adverse events or systemic complications were reported during the 60-day follow-up period. Mild edema, erythema, and ecchymosis resolved spontaneously within 48–72 h. At 60 days, all patients showed natural improvement in facial appearance, with better midface and lower-face balance, increased skin brightness, improved texture, and no overcorrection or alteration of facial expression. Instrumental evaluations supported the clinical findings, showing improvements in skin regularity, chromatic uniformity, microrelief, and soft-tissue distribution; Conclusions: This preliminary case series suggests that the PATH protocol may represent a coherent multimodal strategy for integrated facial rejuvenation. The main clinical lesson is that a sequential, depth-oriented, and individualized approach may achieve natural aesthetic improvement. No serious adverse events were reported in the three patients during the 60-day follow-up period; however, the limited sample size and short follow-up do not allow definitive conclusions regarding safety. Further controlled studies with larger samples and longer follow-up are needed to confirm these exploratory findings.